2021
DOI: 10.1210/clinem/dgab586
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Components of the Inflammasome Machinery After Bariatric Surgery: Novel Targets for a Chronic Disease

Abstract: Background Obesity is a metabolic-chronic disease with important associated morbidities and mortality. Bariatric-surgery is the most effective treatment for maintaining long-term weight-loss in severe obesity and consequently for decreasing obesity-related complications, including chronic inflammation. Aim To explore changes in components of the inflammasome-machinery after bariatric-surgery and their relations with clinical/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…A 48.48 Dynamic Array based on microfluidic technology (Fluidigm, San Francisco, CA, USA) was developed and implemented to determine, simultaneously, the expression of 48 transcripts in 45 samples, following the same methods recently described [13,25]. Specific primers for human transcripts of the inflammasome machinery, including NLR-/NOD-like receptors (n = 7), regulators of inflammasome activation (n = 15), cytokines and inflammation/apoptosis-related components (n = 18) as well as cell-cycle and DNAdamage regulators (n = 5) have been specifically designed and validated as previously reported [26]. In addition, three housekeeping genes were used.…”
Section: Analysis Of Components Of the Inflammasome Machinery By Qpcr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A 48.48 Dynamic Array based on microfluidic technology (Fluidigm, San Francisco, CA, USA) was developed and implemented to determine, simultaneously, the expression of 48 transcripts in 45 samples, following the same methods recently described [13,25]. Specific primers for human transcripts of the inflammasome machinery, including NLR-/NOD-like receptors (n = 7), regulators of inflammasome activation (n = 15), cytokines and inflammation/apoptosis-related components (n = 18) as well as cell-cycle and DNAdamage regulators (n = 5) have been specifically designed and validated as previously reported [26]. In addition, three housekeeping genes were used.…”
Section: Analysis Of Components Of the Inflammasome Machinery By Qpcr...mentioning
confidence: 99%
“…Preamplification, exonuclease treatment and qPCR dynamic array based on microfluidic technology were implemented following the manufacturer's instructions using the Biomark System and the Real-Time PCR Analysis Software 3.0 (Fluidigm), as previously described [26][27][28]. The expression level of each transcript was adjusted by a normalization factor (NF) obtained from the expression levels of two different housekeeping genes (beta actin (ACTB) and glyceraldehyde−3-phosphate dehydrogenase (GAPDH)) using Genorm 3.3.…”
Section: Analysis Of Components Of the Inflammasome Machinery By Qpcr...mentioning
confidence: 99%
“…In contrast, a study reported that NLRP3 expression in SAT, VAT, and liver of 21 patients is not affected by weight loss after 6 months of laparoscopic adjustable gastric banding (despite a decrease in the expression of IL‐1β) [105]. No other studies evaluated the effect of inflammasomes, diet, and weight loss in humans [106].…”
Section: Weight Loss Nutrition and Exercisementioning
confidence: 99%
“…The available studies demonstrated NLRP12 implicated in hypertension, obesity, metabolic syndrome, in ammatory bowel disease, alcoholic liver injury, depression [6,[11][12][13][14]. Shared genetic factors, overlapping chronic in ammatory processes, and abnormal immunomodulatory mechanisms may contribute to the multiple comorbidities of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP12 is primarily expressed in myeloid cells, including macrophages, dendritic cells, monocytes, and neutrophils, comprising of a central nucleotidebinding domain (NBD), an N-terminal pyrin domain (PYD), and a C-terminal leucine-rich repeat (LRR) domain [8]. NLRP12 can participate in in ammasome-mediated in ammation or function as a negative regulator to suppress in ammation, distinguishing it from other members of the NLR family and conferring upon it a dual role in modulating in ammatory responses [9,10].The available studies demonstrated NLRP12 implicated in hypertension, obesity, metabolic syndrome, in ammatory bowel disease, alcoholic liver injury, depression [6,[11][12][13][14]. Shared genetic factors, overlapping chronic in ammatory processes, and abnormal immunomodulatory mechanisms may contribute to the multiple comorbidities of psoriasis.…”
mentioning
confidence: 99%